Phloretin, an Apple Phytoalexin, Affects the Virulence and Fitness of Pectobacterium brasiliense by Interfering With Quorum-Sensing - Pun, Manoj; Khazanov, Netaly; Galsurker, Ortal; Weitman, Michal; Kerem, Zohar; Senderowitz, Hanoch; Yedidia, Iris (Frontiers in Plant Science, 2021)
Phloretin is a phenolic phytoalexin from apple that is associated with plant defense against bacterial fire blight. The effects of different concentrations of phloretin (all below the minimal inhibitory concentration) were tested on Pectobacterium brasiliense, an emerging soft-rot pathogen of potato and vegetable crops. Phloretin interfered effectively with quorum-sensing (QS), a population density-dependent system that exploits chemical signaling to synchronize virulence and host infection. Exposure of P. brasiliense to phloretin significantly inhibited biofilm formation, secretion of plant cell wall-degrading enzymes, the motility and production of acyl–homoserine lactone (AHL) signaling molecules and, subsequently, considerably impaired virulence. Application of phloretin to a QS-negative Escherichia coli strain (DH5α) that had been transformed with an AHL synthase (ExpI) from P. brasiliense inhibited AHL production, as demonstrated using two biosensors, Chromobacterium violaceaum CV026 and E. coli pSB401. Expression analysis of virulence-related genes revealed downregulation of QS and motility genes following exposure to phloretin. These results support the inhibition of ExpI activity by phloretin. Docking simulations were used to predict the molecular associations between phloretin and the active site of ExpI, to suggest a likely mode of action for the compound’s inhibition of virulence.